Kingdom of the Netherlands-Netherlands : Report on Observance of Standards and Codes-FATF Recommendations for Anti-Money Laundering and Combating the Financing of Terrorism. (IMF Staff Country Reports; Country Report ;, 2011)
There is terrorism and terrorist financing (TF) risk, but it appears limited based on available information. The Netherlands has criminalized money laundering (ML) fully in line with the requirements under the Vienna and Palermo Conventions. The Netherlands has a long-standing financial intelligence unit (FIU), which is one the founding members of the Egmont Group of FIUs and enjoys high trust for its professionalism, both domestically and internationally. The suspicious transaction reporting requirement needs to be strengthened to ensure that suspicious transactions are reported promptly to the FIU.